MRI evidence of acute inflammation in leukocortical lesions of patients with early multiple sclerosis. (15th August 2017) - Maranzano, Josefina; Rudko, David A.; Nakamura, Kunio; Cook, Stuart; Cadavid, Diego; Wolansky, Leo; Arnold, Douglas L.; Narayanan, Sridar
Abstract : Objective: To identify gadolinium-enhancing lesions affecting the cortex of patients with early multiple sclerosis (MS) and to describe the frequency and evolution of these lesions. Methods: We performed a retrospective, observational, longitudinal analysis of MRI scans collected as part of the Betaseron vs Copaxone in Multiple Sclerosis with Triple-Dose Gadolinium and 3T MRI Endpoints (BECOME) study. Seventy-five patients with early-stage MS were scanned monthly, over a period of 12–24 months, using 3T MRI after administration of triple-dose gadolinium. A total of 1, 188 scans were included in the analysis. A total of 139 were selected using an image pipeline algorithm that integrated the image information from cortical gray matter masks and gadolinium-enhancing lesion masks. These scans were evaluated to identify gadolinium-enhancing lesions affecting the cortex. Results: The total number of gadolinium-enhancing lesions was 2, 044. The number of gadolinium-enhancing lesions affecting the cortex was 120 (6%), 95% of which were leukocortical. The number of patients who showed gadolinium-enhancing lesions affecting the cortex was 27 (36%). The number of gadolinium-enhancing lesions affecting the cortex at baseline was 25 (21%) and the number of new lesions that developed in follow-up scans was 49 (41%). The number of persistent lesions was 46 (38%). Conclusions: The presence of enhancing lesions affecting the cortex and adjacent white matter, although transient and not frequent, suggests that at least some cortical lesions are related to blood–brain barrier disruption. Our data support the concept that there may be an acute inflammatory phase in the development of leukocortical MS lesions. Clinicaltrials.gov identifier: NCT00176592.